Spectroscopic properties and energy transfer in Nd3+/Yb3+ co-doped yttrium aluminum garnet. (3rd May 2021) - Song, Yan-Jie; Liu, Qian-Qian; Zong, Nan; Wang, Zhi-Min; Cui, Da-Fu; Zhang, Shen-Jin; Bo, Yong; Peng, Qin-Jun
Abstract: High-quality Nd, Yb:YAG crystal with 5 at. % Yb 3+ and 0.5 at. % Nd 3+ was grown using the Czochralski method. A complete optical characterization was reported including absorption, excitation spectra and luminescence lifetime measurements at room temperature and emission spectra at temperatures ranging from 300 K to 800 K. The emission spectra of Nd 3+ /Yb 3+ co-doped YAG were measured for different excitation wavelengths 808 nm and 940 nm. The presence of Yb 3+ emission after excitation in the 4 F5/2 and 4 F3/2 levels of Nd 3+ together with the 4 I9/2 → 4 F5/2 and 4 I9/2 → 4 F3/2 bands of Nd 3+ in the excitation spectra of Yb 3+ ions confirm that energy transfer occurs from Nd 3+ to Yb 3+ . On the other hand, the back transfer from Yb 3+ to Nd 3+ can be neglected. This conclusion is also in agreement with the vanishing overlap between the Yb 3+ emission and Nd 3+ absorption. The analysis of the luminescence decay curves obtained after pulsed excitation has been used to further explore energy transfer processes and the interaction mechanism.